2020
DOI: 10.1039/d0ra07566c
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-mediated formal [3 + 2] annulation for synthesis of furocoumarin from oxime esters

Abstract: A novel synthesis of furocoumarins was developed by a reaction between oxime esters and 4-hydroxycoumarins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…To our knowledge, this represents the first synthesis of furans from oxime esters. 20 3-Cyanofurans are useful blocks for synthesizing complex molecules 21 and have shown interesting UV-absorbing properties; 22 thus, the development of novel protocols to access those heterocycles is an attractive goal. 23 When the transformation was applied to the formerly synthesized oximes 1 and others oxime esters, these molecules reacted with 2b to provide a wide range of furans in a more efficient fashion than was observed in the corresponding syntheses of pyrroles described above (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this represents the first synthesis of furans from oxime esters. 20 3-Cyanofurans are useful blocks for synthesizing complex molecules 21 and have shown interesting UV-absorbing properties; 22 thus, the development of novel protocols to access those heterocycles is an attractive goal. 23 When the transformation was applied to the formerly synthesized oximes 1 and others oxime esters, these molecules reacted with 2b to provide a wide range of furans in a more efficient fashion than was observed in the corresponding syntheses of pyrroles described above (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…[141] Pham and co-workers developed the synthesis of furocoumarin by promoting a reaction between oxime esters and 4hydroxycoumarin via an Iodine-mediated formal [3 + 2] annulation strategy (Scheme 78). [142] During the mechanistic investigation of this reaction, it was observed that the reaction first proceeds via the in-situ generation of the free radical intermediate by the reaction of oxime ester and iodine following a SET mechanism to produce α-iodoimine which finally assists the ring-closing step to furnish the annulated product in moderate to good yield. The developed iodinemediated metal-free approach shows good functional group tolerance to produce diverse ranges of furocoumarins.…”
Section: Metal-free Route For the Synthesis Of Furocoumarin And Its D...mentioning
confidence: 99%
“…Scheme 1 shows some selected approaches through intermolecular reactions for the syntheses of furo [3,2-c]chromenone derivatives from 4hydroxycoumarin (2a). [5][6][7][8][9][10][11][12][13] These furo [3,2-c]chromenone derivatives were obtained by metal-catalyzed or microwave-induced reactions of 4-hydroxycoumarin (2a) with appropriate reacting partners.…”
Section: Cluster Synlettmentioning
confidence: 99%